2017
DOI: 10.3121/cmr.2017.1365
|View full text |Cite
|
Sign up to set email alerts
|

Mid-Upper-Arm Circumference and Arm-to-Height Ratio to Identify Obesity in School-Age Children

Abstract: Background:In resource-poor settings, anthropometric parameters are evaluated as potential alternatives to the body mass index (BMI) for detecting overweight and obesity in children. To this end, the mid-upperarm circumference (MUAC) and the mid-upper-arm circumference-to-height ratio (AHtR) were evaluated as proxies to BMI in Thai school-age children.Study design: An observational, cross-sectional study was performed on school-aged children.Participants: Children in grades 1 through 6 at all public elementary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 19 publications
3
23
1
1
Order By: Relevance
“…In our study, we found that MUAC and AHtR were associated with increased risk for all high blood pressure conditions except isolated EBP in boys, while only diastolic HT was associated in girls. These results are compatible with previous studies and support that MUAC and AHtR can be used to screen high blood pressure [31,32].…”
Section: Changes In Ht Frequency With Other Anthropometric Evaluationsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, we found that MUAC and AHtR were associated with increased risk for all high blood pressure conditions except isolated EBP in boys, while only diastolic HT was associated in girls. These results are compatible with previous studies and support that MUAC and AHtR can be used to screen high blood pressure [31,32].…”
Section: Changes In Ht Frequency With Other Anthropometric Evaluationsupporting
confidence: 93%
“…In addition, a number of studies have reported that SFT measurements can be used to assess the body fat ratio by quantifying subcutaneous fat tissue [27,28]. Therefore, there is a need for investigations for the value of other anthropometric measurements such as midupper arm circumference (MUAC), WC, SFT, and WHtR, which are predictors of body fat ratio and regional fat mass, on blood pressure, the risk of cardiovascular disease [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Hip circumference was measured at the widest point as described by Huang et al [23]. Arm circumference was evaluated at midpoint between olecranon and acromial process on the upper left-arm with the subject in standing position [24], and the calf was measured with the participant seated, knee bent at a ninety-degree angle to the floor and this was considered the point of largest calf circumference [25].…”
Section: Methodsmentioning
confidence: 99%
“…choose appropriate hypoglycemic agents could lead to better control of hyperglycemia and eventually reduce the mortality in diabetes. In Rerksuppaphol S' study, MUAC was suggested to be a simple and accurate parameter to identify overweight and obesity in Thai school-age children [33]. In an observational, multinational cross-sectional study with 7337 children aged 9-11 years, MUAC was shown to be a suitable method to detect obesity in children [34].…”
Section: Plos Onementioning
confidence: 99%